2009
DOI: 10.1007/s10236-008-0174-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of waves, currents and tides, and wave-energy impact on the beach area of Sylt Island

Abstract: Erosion due to waves is an important and actual problem for most coastal areas of the North Sea. The objective of this study was to estimate the impact of wave action on the coastline of Sylt Island. From a 2-year time series (November 1999 to October 2001) of hydrological and wave parameters generated with a coupled wave-current modelling system, a period comprising storm 'Anatol' (3-4 December 1999) is used to investigate the effects of waves on currents and water levels and the input of wave energy into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Until now, the impact of wave processes on the circulation and mixing in the Baltic Sea has seldom been studied, compared for example to the North Sea (Pleskachevsky et al 2009;Pleskachevsky et al 2011;Grashorn et al 2015). Axell (2002) studied the impact of Langmuir circulation on vertical distribution of salinity and found that the thickness of the upper mixed layer deepens by 8 m in the southern Baltic Sea.…”
Section: Wave Effects On Circulationmentioning
confidence: 98%
“…Until now, the impact of wave processes on the circulation and mixing in the Baltic Sea has seldom been studied, compared for example to the North Sea (Pleskachevsky et al 2009;Pleskachevsky et al 2011;Grashorn et al 2015). Axell (2002) studied the impact of Langmuir circulation on vertical distribution of salinity and found that the thickness of the upper mixed layer deepens by 8 m in the southern Baltic Sea.…”
Section: Wave Effects On Circulationmentioning
confidence: 98%
“…Also, the mean flow will be affected by the addition of momentum and mass fluxes. With variation in water level, the depth felt by the waves also changes in the coastal region, thereby modifying the shallow water effects on the waves (Pleskachevsky et al, 2009). Liu et al (2016) Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the water level has an influence on waves, by changing the depth felt by waves (e.g. Pleskachevsky and Kapitza, 2009). Conversely, the currents can be strongly forced and modified by waves.…”
Section: Introductionmentioning
confidence: 96%